Rancang Bangun Double Hull Unmanned Surface Vehicle dengan Pengiriman Data Melalui LoRa - M. Daffa El-Khaq; Diana Alia; Diyah Purwitasari (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
In the era of maritime technology, Unmanned Surface Vehicles (USVs) are becoming the main vehicles on the water surface, controlled from land and capable of transmitting live data. USVs have a wide range of survey and exploration applications, relying on hydrographic knowledge for accurate mapping. USV development has adopted a double hull design, improving stability and wave resistance. Survey data transmission requires advanced technology, with Long Range (LoRa) technology being the solution for long distance data transmission with low power consumption. LoRa utilisation is expected to increase the efficiency of USVs in hydrographic surveys. The research and development (R&D) research method is used as the main approach in this research with the aim of creating and developing USVs that can increase efficiency in hydrographic surveys. The USV is equipped with an RPM sensor and flowmeter used to monitor the movement control of the USV in the waters. In addition, a depth detector is used to monitor the topography of the seabed. In order for this USV to run using a remote control that is controlled from land. The USV drive consists of a BLDC motor connected to the propeller and a servo motor connected to the ship's rudder. Furthermore, the data taken from the sensor is sent via LoRa to be delivered to the ground station. From the USV test results, it was found that the data transmission range with LoRa Ra-02 under Line of sight (LOS) conditions was 340 metres while under Non Light of sight (NLOS) conditions it was around 200 metres. The average speed travelled by USV is 0.616 km/hour in operational survey conditions and can be faster in non-operational survey conditions. The error value of the RPM sensor is obtained at 1.604% with a reading accuracy of 98.936%.